Desain Kurikulum Pendidikan Agama Kristen Keluarga untuk Mengimplementasikan Sakramen Perjamuan Bersama Anak Berdasarkan Model Backward Design - Hidayat, Udin Firman; Rantung, Djoys Anneke; Naibaho, Lamhot (SEKOLAH TINGGI AGAMA KRISTEN TERUNA BHAKTI, 2023)
This research is conducted as an effort to design a Christian Religious Education (PAK) Family curriculum specifically developed to implement the sacrament of Communion with children. The sacrament of Communion with children positively impacts parents' awareness of their role in educating their children's faith. In practice, parents are responsible for providing understanding and preparing their children's involvement in the sacrament of Communion. In line with this specific objective, the Backward Design model is considered more appropriate because